Ionic and electronic transport in calcium-substituted LaAlO3 perovskites prepared via mechanochemical route. Issue 16 (December 2019) - Fabián, Martin; Arias-Serrano, Blanca I.; Yaremchenko, Aleksey A.; Kolev, Hristo; Kaňuchová, Mária; Briančin, Jaroslav
Abstract: The present work explores mechanosynthesis of lanthanum aluminate-based perovskite ceramics and corresponding effects on ionic-electronic transport properties. La1- x Ca x AlO3-δ ( x  = 0.05–0.20) nanopowders were prepared via one-step high-energy mechanochemical processing. Sintering at 1450 °C yielded dense ceramics with submicron grains. As-prepared powders and sintered ceramics were characterized by XRPD, XPS and SEM. Electrochemical studies showed that partial oxygen-ionic conductivity in prepared La1- x Ca x AlO3-δ increases with calcium content up to 10 at.% in the lanthanum sublattice and then levels off at ∼6 × 10 −3 S/cm at 900 °C. La1- x Ca x AlO3-δ ceramics are mixed conductors under oxidizing conditions and ionic conductors with negligible contribution of electronic transport in reducing atmospheres. Oxygen-ionic contribution to the total conductivity is 20–68% at 900 °C in air and increases with Ca content, with temperature and with reducing p(O2 ). Impedance spectroscopy results showed however that electrical properties of mechanosynthesized La1- x Ca x AlO3-δ ceramics below ∼800 °C are determined by prevailing grain boundary contribution to the total resistivity.